Bureaucratic overheating is a parasite hampering modern clinical research – a viewpoint from the 'belly of the beast'. Issue 4 (April 2019) - Humaidan, Peter; Haahr, Thor
Abstract: Clinical researchers in Europe are experiencing an increasing amount of bureaucracy, which in our eyes has now reached surrealistic heights, hampering the future of research, and thus, the development of new treatment regimens and advances in clinical research. In the long term, the current approval and control processes will negatively impact patient care, education, academia and the health economy of our countries. Thus, a debate is necessary including not only healthcare workers, but also politicians and patients.